Fuzzy Sliding Mode Control of PEM Fuel Cell System for Residential Application - Mahdi Mansouri; Mohammad Ghadimi; Kamal Abbaspoor Sani (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Proton exchange membrane fuel cells (PEMFCs) are receiving more attention compared with other sources of power generation. Maintaining a fuel cell system requires excellent system control to receive the best operating. Therefore, in this paper a dynamic model of a (PEMFC) for residential power generation is applied. The model proposed includes the fuel cell stack model, power condition unite that consists of the methanol reformer model and DC-AC inverter model. According to power output of (PEM) fuel cell system, a fuzzy sliding mode controller which contains the characteristics of fuzzy control and sliding mode control is addressed, in order to modify the hydrogen flow feedback from the terminal load. In addition, this combined controller is used to improve stability by fuzzy reasoning to control the output variation that reduces chattering and increase the speed of tracking by reasoning of sliding mode control. Consequently, the dynamical behavior of system with FSMC is more improved as compared to the FLC and PI controller in terms of rate of hydrogen flow, output AC voltage and output power of FC and it is shown that the proposed controller can achieve better control effect than other controllers.